Evaluación de cinco insecticidas para el control de Pinnaspis aspidistrae (Signoret) en (Persea americana Mili) cultivares hass y ettinger en Alto Salaverry La Libertad. - Polo Salinas, Toribio (2014)
The present experimental work "Evaluation of five Insecticides for the control of Pinnaspis aspidistrae (Signoret) in Persea American Mil! Cultivated Hass and Ettinger in high Salaverry the freedom carry out during the months of September of the 2011 to October of the 2012, in the found of the agricultura! company GREEN PERU. The main goal was to evaluate the behaviour of five insecticides in the control of Pinnaspis aspidistrae (Signoret) in two avocados cultivated Hass and Ettinger The levels of study were Movento, Lancer, Epingle, wonder, and the combination of Lancer with Dorsan. The application realize in the states of cuajado brotamiento ofthe phenology ofthe crop. A randomized block design was used with two replicates finding that the best treatment for the control ofthe stadiums nymph, pupas and adults to was the combination ofLancer 0.25 1/cil. With Dorsan 0.5 L/cil. Followed ofthe Movento 0.125 L/cil. And the treatment that present the minor control was Wonder 0.4 L/cil. Concluding that in the three stadiums of the plaga studied the combination Lancer 0.25 L/cil. With Dorsan 0.5 L/cil present the best control for the stadiums of nymphs, pupas and adults. The treatment with Movento 0.125 L/cil. Reduced the density poblacional in the stadiums ofnymph and pupa and the treatment with Lancer 0.25 L/cil. presenta buen alone control in adults ofthe plaga in both cultivated.